Inisiasi Pasca Tambang Menuju Desa Wisata Perlang (Studi di Desa Perlang, Lubuk Besar, Provinsi Kepulauan Bangka Belitung) - Sinabutar, Michael Jeffri; Ramadhani, Tiara; Ulum, Miftahul (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Local initiatives in improving village conditions, starting from social, cultural and economic aspects as a form of community concern and sovereignty over all potential human resources and natural resources. A serious challenge faced by local communities is to ensure balance and sustainability of the local economy. Development could be a threat to local communities, but on the other hand it is an opportunity to build an independent village. Ignoring former mining or tin mining areas is not a sign that there is no guarantee of prosperity, it should be a serious challenge in developing villages. One area that is capable of innovation and creativity in local economic development is the Perlang Tourism Village. This area later became one of the icons and tourist destinations in the Bangka Belitung Islands. This research aims to find out the roots of local initiatives to develop post-mining areas, local initiative models, and how various interests in the local area meet, so as to create a Tourism Village. The approach taken is to use a Deliberative Democracy frame in the Perlang Village community, involving several important village actors, namely the Village Government, Community Leaders, Pokdarwis, and interested actors.